STRATEGI GURU PAI DALAM MENGATASI PERILAKU KURANG DISIPLIN SISWA SDN - Muhammad Abdur Rosyid (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Student discipline is a fundamental aspect of character development and plays an important role in supporting the learning process. However, various forms of undisciplined behavior, such as arriving late, failing to complete assignments, violating school regulations, and paying insufficient attention during lessons, are still frequently found in elementary schools. This study aims to analyze the strategies implemented by Islamic Religious Education (PAI) teachers in overcoming students’ undisciplined behavior, identify the factors influencing such behavior, and examine the impact of these strategies at SDN 2 Ngantru. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the principal, PAI teacher, and students. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured using source and technique triangulation. The findings indicate that PAI teachers implemented several strategies, including role modeling, habituation, advice and motivation, continuous supervision, educational rewards and punishments, and collaboration with parents. The factors influencing students’ undisciplined behavior include internal factors, such as low self-awareness and learning motivation, and external factors, including family environment, peer influence, and technological development. These strategies positively contributed to improving students’ discipline, responsibility, compliance with school regulations, and religious character. Therefore, the study concludes that the consistent implementation of educational, preventive, and corrective strategies by PAI teachers effectively supports the development of disciplined behavior and creates a more conducive learning environment at SDN 2 Ngantru. ABSTRAK Perilaku kurang disiplin siswa masih menjadi permasalahan yang sering dijumpai di sekolah dasar dan dapat menghambat proses pembelajaran serta pembentukan karakter peserta didik. Guru Pendidikan Agama Islam (PAI) memiliki peran strategis dalam menanamkan nilai-nilai kedisiplinan melalui berbagai pendekatan yang sesuai dengan karakteristik siswa. Penelitian ini bertujuan untuk mendeskripsikan strategi guru PAI dalam mengatasi perilaku kurang disiplin siswa, mengidentifikasi faktor-faktor yang memengaruhi perilaku tersebut, serta menganalisis dampak strategi yang diterapkan di SDN 2 Ngantru. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dengan informan yang terdiri atas kepala sekolah, guru PAI, dan siswa. Analisis data dilakukan melalui reduksi data, penyajian data, serta penarikan kesimpulan, sedangkan keabsahan data diuji menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa strategi guru PAI dilaksanakan melalui keteladanan, pembiasaan, pemberian nasihat dan motivasi, pengawasan, penerapan reward dan punishment yang bersifat edukatif, serta kerja sama dengan orang tua. Faktor yang memengaruhi perilaku kurang disiplin meliputi faktor internal berupa rendahnya kesadaran dan motivasi siswa serta faktor eksternal berupa lingkungan keluarga, teman sebaya, dan perkembangan teknologi. Penerapan strategi tersebut memberikan dampak positif terhadap peningkatan kedisiplinan, tanggung jawab, kepatuhan terhadap tata tertib sekolah, serta pembentukan karakter religius siswa. Dengan demikian, strategi guru PAI terbukti berkontribusi dalam membangun budaya disiplin yang mendukung terciptanya lingkungan belajar yang kondusif di SDN 2 Ngantru.